You may use the following alternative method to convert the standard form of quadratic equation into its factored form, such that:

`ax^2 + bx + c = a(x - x_1)(x - x_2)`

`x_1,x_2 ` represent the solutions to the given equation

Hence, you need to evaluate the solutions to quadratic equation `x^2+ 4x - 5 = 0` using quadratic formula, such that:

`x_(1,2) = (-4+-sqrt(16+20))/2 => x_(1,2) = (-4+-sqrt36)/2`

`x_(1,2) = (-4+-6)/2 => x_1 = 1 ; x_2 = -5`

Replacing `a = 1 ` and `x_1 = 1 ; x_2 = -5 ` in factored form of the given quadratic equation, yields:

`x^2+ 4x - 5 = (x - 1)(x + 5)`

**Hence, evaluating the factored form of the given quadratic equation, yields **`(x - 1)(x + 5).`

The expression x^2 + 4x - 5 has to be factored.

x^2 + 4x - 5

= x^2 + 5x - x - 5

= x(x + 5) - 1(x + 5)

= (x - 1)(x + 5)

**The factored form of x^2 + 4x - 5 = (x - 1)(x + 5)**